1992
DOI: 10.1093/jn/122.10.1952
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor-Mediated Functions in Porcine Adipose Tissue Are Not Affected Differently by Saturated vs. Unsaturated Dietary Fats

Abstract: Young postweaning pigs were fed a high fat diet containing beef tallow (saturated fat) or corn oil (unsaturated fat). Adipose tissue was used to measure adipocyte size and number of cells per gram of tissue, ligand binding by beta-adrenergic receptors and lipolytic and palmitate esterification rates. Pigs fed the saturated fat diet had more saturated and monounsaturated fatty acids and less polyunsaturated fatty acid in the crude membrane fraction. Adipocytes were larger in pigs fed the saturated fat diet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the previous study about the lipolytic activity of the same samples that we used in the present research (Martin et al, 2006), dietary MUFA did not exert any effect on the activity of any of the lipolytic enzymes assayed in muscle tissue. Other studies as well have found no difference between the effects of saturated or unsaturated fats on lipolysis in swine adipose tissue (Mersman et al, 1992).…”
Section: Quantitative Changes In the Fatty Acid Contents (Excluding Cmentioning
confidence: 82%
“…In the previous study about the lipolytic activity of the same samples that we used in the present research (Martin et al, 2006), dietary MUFA did not exert any effect on the activity of any of the lipolytic enzymes assayed in muscle tissue. Other studies as well have found no difference between the effects of saturated or unsaturated fats on lipolysis in swine adipose tissue (Mersman et al, 1992).…”
Section: Quantitative Changes In the Fatty Acid Contents (Excluding Cmentioning
confidence: 82%
“…Most suggest that diets rich in PUFA promote greater lipolytic activity than saturated fats (Su & Jones, 1993;Eynard et al 1998). On the other hand, some have found no difference on lipolysis between SFA and PUFA (Mersman et al 1992), or just between different SFA (Portillo et al 1999) or even, under particular circumstances, a lower lipolytic activity of the PUFA (Mersman et al 1992). However, most studies were not oriented to evaluating the role of the n-9 fatty acids in lipolytic activity, but rather the n-6 or n-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies suggest that diets rich in polyunsaturated fatty acids (PUFA) promote greater lipolytic activity than diets rich in saturated fatty acids (SFA) (Su & Jones, 1993;Raclot & Oudart, 1999. However other studies have either found no difference between the effect of saturated and unsaturated fats on lipolysis (Mersman et al 1992) or differences just between different saturated fats (Portillo et al 1999) or even, under certain circumstances, a lower lipolytic activity of the unsaturated fats (Mersman et al 1992). Recent studies, however, have shown that the molecular structure of fatty acids influences their release from the adipocyte, both in vivo and in vitro, with the mobilisation of the PUFA being greater than the MUFA and the SFA (Conner et al 1996;Raclot & Oudart, 1999.…”
mentioning
confidence: 99%
“…The effects of the experimental diets on NOR-stimulated lipolysis in adipocytes from within 5 mm of lymph nodes (i.e. perinodal and middle samples) were not anticipated from previous studies (Mersmann et al 1992(Mersmann et al , 1995 on the action of dietary lipids on the adrenergic receptors of adipocytes themselves. Recent discoveries about the relationship between membrane structure and its capacity to support receptors and secretion vesicles (Simons & Ikonen, 1997) suggest that substitution of fatty acids in membrane phospholipids may underlie the effects reported here.…”
Section: The Effects Of Dietmentioning
confidence: 60%
“…Immune stimulants such as lipopolysaccharide (LPS) can alter the expression of b 3 -adrenergic receptor mRNA in large murine adipose depots (Berkowitz et al 1998), but no effects on sensitivity to catecholamines have been demonstrated. Metabolic regulators of adrenergic stimulation of lipolysis have been extensively studied and various agents have been identified (Björntorp, 1996;El Hadri et al 1997;Orban et al 1999), but dietary lipids were not thought to be among them: Mersmann et al (1992Mersmann et al ( , 1995 found only minimal effects of dietary fats on the abundance or functioning of adrenergic receptors in pig adipocytes, although their experimental diets induced marked differences in the fatty acid compositions of the adipocyte membranes. However, these studies were limited to adipocytes from subcutaneous or large intra-abdominal depots that are not associated with lymphoid tissue.…”
mentioning
confidence: 99%